Assessment of bridges' expansion joints in Egypt - Badawy, Abdelhay Mohamed (AUC Knowledge Fountain, 2017)
Bridges play a vital role in resolving transportation problems in Egypt. The objective of this research is to predict the conditions of bridges expansion joints, with the aim of proposing appropriate maintenance and repair strategies in order to extend their lifespans. A thorough literature review of existing bridges expansion joints maintenance and repair strategies are conducted. Furthermore, visual inspections and surveying of existing bridges expansion joints in Egypt are conducted, with the findings of such observations documented and recorded. Moreover, an expansion joint management system (EJMS) is developed with the aim of recommending the optimum maintenance strategy for bridges that optimizes annual condition index (ACI) and cost. This model uses a combination of Fuzzy Logic (FL) and Genetic Algorithm (GA) in order to provide optimal recommendations. In addition, a transition matrix for predicting deterioration of expansion joints EJ using Markov Chain (MC) is developed. In order to test the model, several case studies of existing bridges in Egypt are used and the results are assessed against those documented through visual inspection. The comparison indicated that the developed EJMS is efficient in predicting the bridge EJs condition, where there is a deviation of 5% between the predicted condition from EJMS and the actual conditions observed through visual inspections. In addition, EJMS can play an important role in supporting decision makers in selecting the optimum maintenance and repair strategy that would maximizes the overall condition of expansion joints while meeting a certain budget constraint.